Imaging Biomarkers to Predict and Evaluate the Effectiveness of Immunotherapy in Advanced Non-Small-Cell Lung Cancer - Liu, Ying; Wu, Minghao; Zhang, Yuwei; Luo, Yahong; He, Shuai; Wang, Yina; Chen, Feng; Liu, Yulin; Yang, Qian; Li, Yanying; Wei, Hong; Zhang, Hong; et al. (Frontiers in Oncology, 2021)
Objective: We aimed to identify imaging biomarkers to assess predictive capacity of radiomics nomogram regarding treatment response status (responder/non-responder) in patients with advanced NSCLC undergoing anti-PD1 immunotherapy. Methods: 197 eligible patients with histologically confirmed NSCLC were retrospectively enrolled from 9 hospitals. We carried out a radiomics characterization from target lesions (TL) approach and largest target lesion (LL) approach on baseline and first follow-up (TP1) CT imaging data. Delta-radiomics feature was calculated as the relative net change in radiomics feature between baseline and TP1. Minimum Redundancy Maximum Relevance (mRMR) and Least Absolute Shrinkage and Selection Operator (LASSO) logistic regression were applied for feature selection and radiomics signature construction. Results: Radiomics signature at baseline did not show significant predictive value regarding response status for LL approach (P=0.10), nor in terms of TL approach (P=0.27). A combined Delta-radiomics nomogram incorporating Delta-radiomics signature with clinical factor of distant metastasis for target lesions had satisfactory performance in distinguishing responders from non-responders with AUCs of 0.83 (95% CI: 0.75-0.91) and 0.81 (95% CI: 0.68-0.95) in the training and test sets respectively, which was comparable with that from LL approach (P=0.92, P=0.97). Among a subset of those patients with available pretreatment PD-L1 expression status (n=66), models that incorporating Delta-radiomics features showed superior predictive accuracy than that of PD-L1 expression status alone (P<0.001). Conclusion: Early response assessment using combined Delta-radiomics nomograms have potential advantages to identify patients that were more likely to benefit from immunotherapy, and help oncologists modify treatments tailored individually to each patient under therapy.